New species and records of Beckidia Sæther (Diptera: Chironomidae) from the Russian Far East - Zorina, Oksa V. (Zootaxa, 2006)
Two new species of Beckidia Sæther, B. biraensis and B. connexa, from the Amur River Basin are described and figured as males. The male of B. tethys (Townes) is redescribed and figured and the species is recorded for the first time from Russia. The generic diagnosis is emended and a key to the males of Beckidia from the Holarctic Region is given.